Synthesis, crystal structure and biological activity of 6-(3-chloropropoxy)-4-(2-fluorophenylamino)-7-methoxyquinazoline. Issue 3 (March 2019) - Cai, Zhi-Qiang; Zhao, Chen-kang; Li, Meng-Yao; Shuai, Xiao-Min; Ding, Hai-Guan; Wang, Qing-Lin; Fu, Jia; Jin, Zheng-Sheng; Li, Shuai; Zhao, Le-Jing
The title compound, 6-(3-chloropropoxy)-4-(2-fluorophenylamino)-7-methoxyquinazoline, was synthesized by selective nucleophilic attack at C-1 of 1-bromo-3-chloropropane by the potassium salt of 4-(2-fluorophenylamino)-7-methoxyquinazolin-6-ol, which was prepared from 7-methoxy-4-oxo-3, 4-dihydroquinazolin-6-yl acetate in three steps. The compound crystallized as an ethyl acetate complex (C20 H21 ClFN3 O3, M r = 405.85), and X-ray crystallography showed that the crystal belongs to the orthorhombic system, space group Pbca with a = 12.7407(4) Å, b = 14.0058(5) Å, c = 21.7726(7) Å, α = 90°, β = 90° and γ = 90°. The whole molecule is stacked into a three-dimensional structure via weak N–H…N hydrogen bonding between molecules. The compound acts as an effective inhibitor on the proliferation of a lung cancer cell line.